The Psychiatric Patient as a Health Resource Consumer: Costs Associated with Electroconvulsive Therapy - Selva-Sevilla, Carmen; Gonzalez-Moral, Maria Luisa; Tolosa-Perez, Maria Teresa (Frontiers in Psychology, 2016)
Background: Clinical practice protocols should consider both the psychological criteria related to a patient’s satisfaction as a consumer of health services and the economic criteria to allocate resources efficiently. An electroconvulsive therapy program was implemented in our hospital to treat psychiatric patients. The main objective of this study was to determine the cost associated with the electroconvulsive therapy sessions implemented in our hospital between 2008 and 2014. A secondary objective was to calculate the cost of sessions that were considered ineffective, defined as those sessions in which electrical convulsion did not reach the preset threshold duration, in order to identify possible ways of saving money and improving satisfaction among psychiatric patients receiving electroconvulsive therapy. Methods: A descriptive analysis of the direct health costs related to electroconvulsive therapy from the perspective of the public health system between 2008 and 2014 was performed using a retrospective chart review. All of the costs are in euros (2011) and were discounted at a rate of 3%. Based on the base case, a sensitivity analysis of the changes of those variables showing the greatest uncertainty was performed. Results: Seventy-six patients received 853 sessions of electroconvulsive therapy. The cumulative cost of these sessions was € 1409528.63, and 92.9% of this cost corresponded to the hospital stay. A total of € 420732.57 (29.8%) was inefficiently spent on 269 ineffective sessions. A sensitivity analysis of the economic data showed stable results to changes in the variables of uncertainty. Conclusions: The efficiency of electroconvulsive therapy in the context outlined here could be increased by discerning a way to shorten the associated hospital stay and by reducing the number of ineffective sessions performed.